Impacto del turismo receptivo en el crecimiento económico de Loreto, periodo 2018 – 2022 - Carrión Rios, Fátima Vanessa (2025)
The main objective of this thesis is to determine the influence of inbound tourism on the economic growth of the Loreto region during the period 2018 2022. A descriptive-correlational approach was used with a non-experimental design, based on the collection and analysis of secondary data from official sources such as the Ministry of Foreign Trade and Tourism (MINCETUR), the National Institute of Statistics and Informatics (INEI), the Central Reserve Bank of Peru (BCRP) and PromPerú. This methodology allowed us to study the variations in the Gross Domestic Product (GDP) of Loreto and the behavior of the arrivals of national and foreign tourists during said period. The study reveals that, although Loreto's GDP grew on average by 1%, domestic tourist arrivals decreased by 5% and foreign tourist arrivals by 7%. Despite fluctuations in inbound tourism, correlation tests indicated that neither domestic nor foreign tourists had a significant impact on the region's economic growth. National tourism represented 73% of arrivals and international tourism 27%, but there was no relevant correlation with GDP. The causes could be the lack of diversification of tourism markets, low spending by tourists and limited infrastructure. The study suggests the need for public policies focused on improving infrastructure and increasing tourism spending to encourage greater economic growth.